PENGELOLAAN PEMBELAJARAN ANAK HIPERAKTIF DALAM SETTING INKLUSI DI RA AL-HASANAH LANGKAPLANCAR - Mina Kusmiati, - (2022)
This research is motivated by the problems that exist in the field, namely there are children who do not want to be silent during the learning process, their limbs are never silent, spin here and there, go up and down chairs and tables, do not stop and do not care about the people around them, this child called hyperactive children. The purpose of this study was to find out how to manage the learning of hyperactive children in an inclusive setting. The method used in this research is a case study, using a qualitative approach, how to obtain data using interviews, observation and documentation. The subjects in this study were hyperactive children and classroom teachers. Data collection techniques using interview guidelines, observation and documentation. The results of this study are schools implementing learning management for hyperactive children starting from the management of learning places, management of teaching materials, management of activities and time, management of students, management of learning resources and management of teaching behavior. The obstacles faced in managing the learning of hyperactive children are the lack of interesting media for each lesson and parents of hyperactive children who rarely take their children to school because they are ashamed to have children with special needs, the solution implemented is that teachers make improvised media and provide guidance to parents of hyperactive children.